Traffic Accident Model Reviewed from The Factors of Driving Behaviour of Surabaya-Gempol Toll Road - Supriyatno, Dadang; Mudjanarko, Sri Wiwoho; Dwiatmoko, Hermanto (International Journal of Integrated Engineering, 2020)
The development of road capacity is not in line with the development of the population and the increase in the number of vehicles. This has become a classic problem of transportation in the big cities of Indonesia, including in East Java Province. The existence of road capacity in accommodating vehicles must be resolved. One way to accommodate the number of vehicles is through the toll road. But comfortable conditions of the toll road can cause accidents. One factor causing this is the driver’s behavior factors, as the toll road is a freeway, they tend to drive carelessly. On the other hand, high planning standards make the difference between toll roads and ordinary highways. Yet barrier-free road does not mean that the traffic accident problem can be resolved properly. This study aims to determine how significant is the influence of driver behavior factor in causing accidents. The methodology is done by analyzing the data using statistical methods. Based on the accident data obtained, a mathematical model with multiple linear regression analysis is made. The model connects the number of traffic accidents on the Surabaya-Gempol toll road with the number of accidents caused by driver factors. The results showed that the factors causing the accident were caused by less anticipated driver factors, carelessness, drowsiness, drunkenness, distance, etcetera. This variable has a significant effect on traffic accidents at Surabaya-Gempol Toll Road by 54%.